Determinasi Dukungan Sosial Dan Kepatuhan Terapi Terhadap Kualitas Hidup Pasien Hemodialisis Berbasis Aplikasi Digital Hd-Care - Karlina, Nonok; Sri Nurcahyati; Munawaroh, Magfirohtul; Tantri Maulani Putri; Terry Melany (Jurnal Kesehatan Mahardika, 2026)
Introduction: Chronic kidney disease is a global health problem that significantly affects the quality of life of hemodialysis patients. Social support and therapy adherence are key determinants, particularly with the use of digital applications such as HD-Care. Purpose: To analyze the determinants of social support and therapy adherence on the quality of life among hemodialysis patients using the HD-Care digital application. Methods: A quantitative observational analytic study was conducted on 83 hemodialysis patients at Permata Kuningan Hospital in 2025. Data were collected using MSPSS, ESRD-AQ, and WHOQOL-BREF. Multiple linear regression analysis was applied with a significance level of 0.05. Results: Social support (p=0.003) and therapy adherence (p=0.000) significantly influenced quality of life. Therapy adherence was the dominant factor (β=0.498). Both variables explained 37.4% of the variance in quality of life (R²=0.374). Conclusions: Social support and therapy adherence play an important role in improving quality of life. Digital-based nursing interventions may enhance patient outcomes.